Media Flashcards Berbantuan Qr Code Untuk Keterampilan Menulis Bahasa Prancis Siswa Kelas XI SMA Negeri 16 Bandar Lampung - Ikhtiarti, Endang; Amalia, Riska Putri; Rini, Setia (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
The research aims to develop a learning medium in the form of Flashcards assisted by QR Codes to enhance the descriptive paragraph writing skills in French for 11th-grade students, focusing on the topic "se présenter." This study employs the Research and Development (RnD) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research instruments used include questionnaires, interviews, and tests. The questionnaires and interviews were utilized to analyze the needs of students and educators, assess material and media testing, and evaluate user trials of the developed learning media. The average score obtained from the material validators was 88.75%, categorized as Very Good (VG). Similarly, the average score from the media validators was 88.75%, also categorized as Very Good (VG), indicating the product is suitable for use. In user trials and tests conducted with a large group, consisting of all 31 students from class XI 4, the average percentage score was 87%, categorized as Very Good (VG) and deemed suitable for use in learning.Kata kunci: Bahasa Prancis, Flashcards, Keterampilan Menulis, Media Pembelajaran, Qr Code, RnD